Augmented reality in cardiovascular education (HoloHeart): assessment of students’ and lecturers’ needs and expectations at Heidelberg University Medical School - Schlegel, Pascal Philipp; Kehrle, Florian; Bugaj, Till Johannes; Scholz, Eberhard P.; Kovacevic, Alexander; Grieshaber, Philippe; Nawrotzki, Ralph; Kirsch, Joachim; Hecker, Markus; Meyer, Anna L.; Seidensaal, Katharina; Do, Thuy; et al. (Applied Sciences, 2025)
Background: A detailed understanding of cardiac anatomy and physiology is crucial in cardiovascular medicine. However, traditional learning methods often fall short in addressing this complexity. Augmented reality (AR) offers a promising tool to enhance comprehension. To assess its potential integration into the Heidelberger Curriculum Medicinale (HeiCuMed), we conducted a needs assessment among medical students and lecturers at Heidelberg University Medical School. Methods: Our survey aimed to evaluate the perceived benefits of AR-based learning compared to conventional methods and to gather expectations regarding an AR course in cardiovascular medicine. Using LimeSurvey, we developed a questionnaire to assess participants’ prior AR experience, preferred learning methods, and interest in a proposed AR-based, 2 × 90-min in-person course. Results: A total of 101 students and 27 lecturers participated. Support for AR in small-group teaching was strong: 96.3% of students and 90.9% of lecturers saw value in a dedicated AR course. Both groups favored its application in anatomy, cardiac surgery, and internal medicine. Students prioritized congenital heart defects, coronary anomalies, and arrhythmias, while lecturers also emphasized invasive valve interventions. Conclusions: There is significant interest in AR-based teaching in cardiovascular education, suggesting its potential to complement and improve traditional methods in medical curricula. Further studies are needed to assess the potential benefits regarding learning outcomes.
Veröffentlicht: 2. August 2025
Gesehen am 15.01.2026